Ham. Issue 2 (2nd July 2016) - Stankus, Tony
ABSTRACT: This article provides a working definition of ham. It identifies ancient Rome as the first Western civilization in which the making and marketing of hams on a large scale is well-documented. The two major modern pathways of curing hams and the major differences in how these hams are sold and served today in Europe and the United States are detailed. Finally, contemporary issues surrounding ham consumption and health are briefly reviewed.